2007
DOI: 10.1121/1.2427117
|View full text |Cite
|
Sign up to set email alerts
|

Variability and uncertainty in masking by competing speech

Abstract: This study investigated the role of uncertainty in masking of speech by interfering speech. Target stimuli were nonsense sentences recorded by a female talker. Masking sentences were recorded from ten female talkers and combined into pairs. Listeners' recognition performance was measured with both target and masker presented from a front loudspeaker (nonspatial condition) or with a masker presented from two loudspeakers, with the right leading the front by 4 ms (spatial condition). In Experiment 1, the sentenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 29 publications
7
50
3
Order By: Relevance
“…It is, however, clear from the present research that speech-in-speech recognition accuracy can display sensitivity to contextual variation as it extends beyond the time-frame of the target signal itself. In contrast to previous work that showed little or no effect of cross-trial variation in acoustic or spatial characteristics known to influence speech-in-speech recognition (e.g., Brungart and Simpson, 2004;Freyman et al, 2007;Jones and Litovsky, 2008), this study has shown sensitivity to contextual variation in terms of the matching or mismatching of the language being spoken in the target and in the background. This sensitivity extended to languages as similar in sound structure as English and Dutch.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…It is, however, clear from the present research that speech-in-speech recognition accuracy can display sensitivity to contextual variation as it extends beyond the time-frame of the target signal itself. In contrast to previous work that showed little or no effect of cross-trial variation in acoustic or spatial characteristics known to influence speech-in-speech recognition (e.g., Brungart and Simpson, 2004;Freyman et al, 2007;Jones and Litovsky, 2008), this study has shown sensitivity to contextual variation in terms of the matching or mismatching of the language being spoken in the target and in the background. This sensitivity extended to languages as similar in sound structure as English and Dutch.…”
Section: Discussioncontrasting
confidence: 47%
“…Whereas previous work focused on contextual variation (i.e., masker uncertainty) in terms of talkers, semantic content or location of the background speech signal (Brungart and Simpson, 2004;Freyman et al, 2007;Jones and Litovsky, 2008), we focus here on background language variation, a dimension of variation that is increasingly common in an era of globalization and that, as mentioned above, previous work has suggested (but not yet indisputably verified) may introduce a source of informational, in addition to energetic masking. Moreover, in an effort to more closely match real-world communicative settings, we use meaningful sentence stimuli with an open set response format, rather than formulaic sentences with a closed-set response format or nonsense sentences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was motivated given the contradictory findings on the contribution of uncertainty to speech recognition between young and old listener groups (Brungart and Simpson, 2004;Freyman et al, 2007;Humes and Coughlin, 2009;Humes et al, 2006;Mackersie et al, 2011;Sommers, 1997). For the competing speech environment, it is well known that target-masker similarity and stimulus uncertainty are associated with informational masking (Durlach et al, 2003;Freyman et al, 2007). Freyman et al (2007) varied the amount of masker uncertainty for a speech-recognition task and expected to observe more informational masking with increasing uncertainty of the masker.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…For the competing speech environment, it is well known that target-masker similarity and stimulus uncertainty are associated with informational masking (Durlach et al, 2003;Freyman et al, 2007). Freyman et al (2007) varied the amount of masker uncertainty for a speech-recognition task and expected to observe more informational masking with increasing uncertainty of the masker. Unexpectedly, they found a relatively small effect of masker uncertainty on nonsense sentence identification for YNH listeners.…”
Section: Purpose Of the Studymentioning
confidence: 99%